The body farm eaudiobook - Cornwell, Patricia (Kay Scarpetta, 2012)
A small town in North Carolina is shaken when an 11-year-old girl is brutally murdered. In this crime, Forensic pathologist Kay Scarpetta sees eerie and disturbing echoes of a serial killer's work. Her investigation will lead her to a macabre research facility and into a truly horrifying world. New York Times best-selling author Patricia Cornwell fills this novel with knife-edged suspense.